Analisis Pengaruh Flash Sale dan Scarcity Messages terhadap Impulsive Buying pada Pengguna Shopee di Kota Solo - Annisa Mutmainah; Moh Rifqi Khairul Umam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
E-commerce is growing rapidly, and businesses are constantly looking for new ways to increase their competitive advantage. In this context, understanding impulsive buying behavior is essential. In holding flash sales and scarcity messages, companies need to identify the effectiveness of the strategies implemented in their marketing practices. The Stimulus-Organism-Response (SOR) model is used so that it can explain the relationship between variables in this study. The purpose of this study is to evaluate the analysis of how Shopee users' impulsive purchases are influenced by flash sales and scarcity messages. The research conducted is quantitative research. The research sample was carried out using the lemeshow formula on Shopee application users. The data collection technique used Non-probability Sampling. The questionnaire was distributed via Google Form to collect data, as well as software or software with SPSS 23 which was used for multiple regression analysis.